The Effect of Career Growth on Employee Turnover Intention in Sarawak Construction Industry - Amelia, Goh Jiaying; Agatha Lamentan, Muda (UNIMAS Publisher, 2023)
This study examines the effect of career growth dimensions (career goal progress, professional ability development, promotion speed, and remuneration growth) on turnover intention in the Sarawak construction industry. Using a quantitative method and cross-sectional design, data was collected through an online survey questionnaire and analysed using multiple regression analysis. Results indicate that career goal progress and professional ability development have a significant effect on turnover intention, while promotion speed and remuneration growth do not have any significant effect on turnover intention. These findings emphasise the importance of career growth opportunities and professional development strategies to enhance employee satisfaction and reduce turnover. Organisations should reassess retention strategies and consider other factors influencing turnover intention to improve employee retention efforts.